1990
DOI: 10.1093/carcin/11.8.1413
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of altered hepatic foci development in rat liver, cytochrome P450 enzyme induction and inhibition of cell-cell communication by DDT and some structurally related organohalogen pesticides

Abstract: The organochlorine pesticide 1,1'-(2,2,2-trichloroethylidene) bis(4-chlorobenzene) (DDT) and four structural analogues (bromopropylate, chlorobenzilate, dicofol and fenarimol) were investigated for their ability to inhibit gap junctional intercellular communication both in the Chinese hamster V79 metabolic co-operation assay and in the scrape-loading/dye-transfer assay in WB-F344 rat liver epithelial cells. The pesticides were also studied for their ability to enhance the development of gamma-glutamyltranspept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
19
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(22 citation statements)
references
References 0 publications
3
19
0
Order By: Relevance
“…For example, metabolism of OPs is influenced by a number of genes including paraoxonase (PON1) and the cytochrome P450s (69,72,75,113,161,278). Recently, polymorphisms in PON1 were associated with increased prostate cancer risk among Finnish men (199).…”
Section: Discussionmentioning
confidence: 99%
“…For example, metabolism of OPs is influenced by a number of genes including paraoxonase (PON1) and the cytochrome P450s (69,72,75,113,161,278). Recently, polymorphisms in PON1 were associated with increased prostate cancer risk among Finnish men (199).…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14][15][16][17][18][19][20][21][22][23] With reference to the excesses reported here, the available experimental and epidemiological data suggest that DDT may act as a multiple cancerogen 24 through different epigenetic mechanisms of action. [25][26][27] Limited evidence is available on the ability of dicofol to induce liver cancer in mouse. 28 As reported for DDT, this chemical is also able to inhibit gap-junctional intercellular communications in rodents and human cell systems.…”
Section: Discussionmentioning
confidence: 99%
“…28 As reported for DDT, this chemical is also able to inhibit gap-junctional intercellular communications in rodents and human cell systems. 25 The available toxicological information on tetradifon only indicate that this compound is weakly positive in sister chromatid exchange assay with human lymphocyte cultures. 29 Specific observations about carcinogenic effects of organochlorine compounds on the prostate gland are very limited.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 According to many previous reports regarding DDT hepatocarcinogenicity and its mechanisms, the number and area of GST-P-positive foci are increased in an in vivo medium-term bioassay of liver carcinogenesis in rats 9 and gap junctional intercellular communication in liver is inhibited in several in vivo and in vitro bioassays. 10 -15 Furthermore, it is suggested that oxidative DNA damage induced by DDT is one of the important factors in hepatocarcinogenesis, since DDT elicits an increase in lipid peroxidation 16 and its inhibition of gap junctional intercellular communication is partially prevented by the antioxidant vitamin E. 17 The hepatic cytochrome P-450 multistage family of microsomal enzymes can be induced by numerous compounds as a phase I metabolizing enzyme, but the oxidative metabolism partially contributes to elicit the carcinogenic potential of some xenobiotics by augmenting oxidative stress.…”
mentioning
confidence: 99%